Will [compact disc, unabridged] - Smith, Will, 1968-; Manson, Mark (Penguin Random House Audio, 2021)
"Will Smith's transformation from a West Philadelphia kid to one of the biggest rap stars of his era, and then one of the biggest movie stars in Hollywood history, is an epic tale, but it's only half the story. Will Smith thought he had won at life: not only was his own success unparalleled, his whole family was at the pinnacle of the entertainment world. Only they didn't see it that way: they felt more like performers in his circus, a seven-days-a-week job they hadn't signed up for. It turned out Will Smiths education wasn't nearly over. This memoir is the product of a profound journey of self-knowledge, a reckoning with all that your will can get you and all that it can leave behind"--Back cover.